Screening for intrinsic capacity impairments as markers of increased risk of frailty and disability in the context of integrated care for older people: Secondary analysis of MAPT. (August 2021) - González-Bautista, Emmanuel; de Souto Barreto, Philipe; Andrieu, Sandrine; Rolland, Yves; Vellas, Bruno; ,
Highlights: The more intrinsic capacity impairments an older person has, the higher is the risk of incident frailty and incident disability. Limited mobility, vision impairment and depressive symptoms are predictors of functional decline. The ICOPE Step1 screening tool can detect people at higher risk of functional decline. Abstract: Aim: This longitudinal secondary analysis of the Multidomain Alzheimer Preventive Trial (MAPT) aimed to test whether the Integrated Care for Older People (ICOPE) Step 1 screening tool is able to identify people at risk of developing frailty and disability in basic (ADL) and instrumental (IADL) activities of daily living among community-dwelling older adults. Participants and setting: Seven hundred and fifty-nine ( n  = 759) non-demented participants of the MAPT aged 70–89 years were assessed in memory clinics in France between 2008 and 2013. Methods: We measured six intrinsic capacity (IC) impairments, adapted from the ICOPE screening tool. We used Cox models to estimate the adjusted hazard ratios of incident frailty and IADL/ADL disability. Incident frailty was defined by Fried's phenotype, and incident disability was measured according to Lawton and Katz for IADLs and ADLs. Results: Limited mobility (HR= 2.97, 95%CI= 1.85–4.76), depressive symptoms (HR= 2.07, 95%CI= 1.03–4.19), and visual impairment (HR= 1.70, 95%CI 1.01–2.86) were associated with a higher incidence of frailty over 5 years. Each additional IC condition demonstrated a positive association with a higher risk of incident frailty, IADL, ADL disability, with risk increased by 47%, 27%, and 23% over 5 years, respectively. Conclusion: Screening for IC impairments identifies older adults at higher risk of incident frailty and incident IADL/ADL disability. It is relevant to screen for these impairments together because the risk of frailty and disability increases with each additional one. ClinicalTrials.gov identifier: NCT00672685